Mialostatin, a Novel Midgut Cystatin from Ixodes ricinus Ticks: Crystal Structure and Regulation of Host Blood Digestion - Kotál, Jan; Buša, Michal; Urbanová, Veronika; Řezáčová, Pavlína; Chmelař, Jindřich; Langhansová, Helena; Sojka, Daniel; Mareš, Michael; Kotsyfakis, Michail (International journal of molecular sciences, 2021)
The hard tick Ixodes ricinus is a vector of Lyme disease and tick-borne encephalitis. Host blood protein digestion, essential for tick development and reproduction, occurs in tick midgut digestive cells driven by cathepsin proteases. Little is known about the regulation of the digestive proteolytic machinery of I. ricinus. Here we characterize a novel cystatin-type protease inhibitor, mialostatin, from the I. ricinus midgut. Blood feeding rapidly induced mialostatin expression in the gut, which continued after tick detachment. Recombinant mialostatin inhibited a number of I. ricinus digestive cysteine cathepsins, with the greatest potency observed against cathepsin L isoforms, with which it co-localized in midgut digestive cells. The crystal structure of mialostatin was determined at 1.55 Å to explain its unique inhibitory specificity. Finally, mialostatin effectively blocked in vitro proteolysis of blood proteins by midgut cysteine cathepsins. Mialostatin is likely to be involved in the regulation of gut-associated proteolytic pathways, making midgut cystatins promising targets for tick control strategies.
Keywords: Cystatins; cystatiny; sekvence aminokyselin; krevní proteiny; Proteolysis; Mice, Inbred BALB C; proteolýza; Female; klíště; myši; kathepsin L; Cathepsin L; Mice; fylogeneze; Blood Proteins; Ixodes; mužské pohlaví; myši inbrední BALB C; zvířata; Ticks; ženské pohlaví; Animals; Male; Digestive System; klíšťata; Phylogeny; Amino Acid Sequence; trávicí systém